The Effect of Product Innovation and Store Atmosphere on The Purchase Decision of Fore Coffee Gayamsari Products in Semarang City with Buying Interest as An Intervening Variable (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to determine the Influence of Product Innovation and Store Atmosphere on Purchase Decisions of Fore Coffee Gayamsari Products in Semarang City with Purchase Interest as an Intervening Variable. The population used in this study were Fore Coffee Consumers and the sample used was 210 Fore Coffee Gayamsari consumers using AMOS 22. These results indicate that there is a positive and significant influence of product innovation on purchasing decisions with a P-value of 0.026 0.050, purchase interest has a positive and significant effect on purchasing decisions with a P-value of 0.006
Keywords: Inovasi Produk; Store Atmosphere; Minat Beli; Keputusan Pembelian